Perencanaan Peningkatan Akses Jalan Bandar Udara Notohadinegoro - Inas Ade Zahra; Akhmad Hasanuddin; Nunung Nuring Hayati; Sonya Sulistyono (Universitas Jember, 2022)
Notohadinegoro Airport access road according to road class is class III road. This road has a length of ± 3 km and a width of 3 m, where the traffic control is 2-way undivided. The direction of development of Notohadinegoro Airport as stated in the development plan document of the Jember Regency Transportation Agency in 2005, one of the development directions is widening the access road to the airport. This research was conducted to plan the improvement of road access to Notohadinegoro Airport. Improved road access is planned to be a 2-lane 2-way road type. The method in planning refers to the 1997 Intercity Road Geometric Planning Procedure, the 2017th Road Pavement Manual method for pavement thickness with a plan year of 20 years, and compiling the cost requirements for this road improvement work. The results were obtained for geometric planning using a road width of 7 m with a median width of 2 m. Planning for flexible pavement obtained surface layer thickness AC-WC = 40 mm, AC-BC = 60 mm, and aggregate foundation layer = 400 mm. Meanwhile, the cost needs to reach Rp. 11,265,996,400.00. Abstrak Akses jalan Bandar Udara Notohadinegoro menurut kelas jalan adalah jalan kelas III. Jalan ini mempunyai panjang ± 3 km dan lebar 3 m, dimana pengaturan lalu lintas adalah 2 arah tak terbagi. Arah pengembangan Bandar Udara Notohadinegoro yang tertuang dalam dokumen rencana pengembangan Dinas Perhubungan Kabupaten Jember pada tahun 2005, salah satu arah pengembangan adalah pelebaran pada akses jalan menuju bandar udara. Penelitian ini dilakukan untuk merencanakan peningkatan akses jalan Bandar Udara Notohadinegoro. Peningkatan akses jalan direncanakan menjadi tipe jalan 2 lajur 2 arah. Metode dalam perencanaan mengacu pada Tata Cara Perencanaan Geometrik Jalan Antar Kota tahun 1997, metode Manual Perkerasan Jalan tahun 2017 untuk tebal perkerasan dengan tahun rencana 20 tahun, dan menyusun kebutuhan biaya pada pekerjaan peningkatan jalan ini. Hasil penelitian diperoleh untuk perencanaan geometrik menggunakan lebar jalan 7 m dengan lebar median 2 m. Perencanaan perkerasan lentur diperoleh tebal lapis permukaan AC-WC = 40 mm, AC-BC = 60 mm, dan lapis pondasi agregat = 400 mm. Sedangkan untuk kebutuhan biaya mencapai Rp. 11.265.996.400,00.